2010
DOI: 10.1007/s00213-010-1919-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical dependence potential of daily tramadol dosing in humans

Abstract: Rationale Tramadol is an atypical, mixed-mechanism analgesic involving both opioid and catecholamine processes that appears to have low abuse potential and may be useful as a treatment for opioid dependence. Objectives The current study assessed the level of physical dependence and opioid blockade efficacy produced by daily maintenance on oral tramadol. Methods Nine residential opioid-dependent adults were maintained on two doses of daily oral tramadol (200 and 800 mg) for approximately 4-week intervals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 26 publications
6
47
0
1
Order By: Relevance
“…In addition, the absence of stimulant-like effects is a further advantage if tramadol is used in a drug-abusing population. These results are in line with several laboratory studies that have supported tramadol as a potential treatment for opioid dependence (Carroll et al, 2006;Lofwall et al, 2007;Lanier et al, 2010) and are also consistent with retrospective studies examining tramadol as a treatment for opioid withdrawal (Tamaskar et al, 2003;Threlkeld et al, 2006). Taken together, these converging lines of work suggest tramadol may be a useful medication for the treatment of patients with low levels of opioid dependence or for the treatment of mild to moderate opioid withdrawal.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the absence of stimulant-like effects is a further advantage if tramadol is used in a drug-abusing population. These results are in line with several laboratory studies that have supported tramadol as a potential treatment for opioid dependence (Carroll et al, 2006;Lofwall et al, 2007;Lanier et al, 2010) and are also consistent with retrospective studies examining tramadol as a treatment for opioid withdrawal (Tamaskar et al, 2003;Threlkeld et al, 2006). Taken together, these converging lines of work suggest tramadol may be a useful medication for the treatment of patients with low levels of opioid dependence or for the treatment of mild to moderate opioid withdrawal.…”
Section: Discussionsupporting
confidence: 88%
“…These preclinical findings are consistent with results from clinical laboratory studies suggesting that tramadol does not produce significant morphine-like effects (Preston et al, 1991;Cami et al, 1994;Adams et al, 2006;Lofwall et al, 2007). Although chronic tramadol administration has the ability to produce physical dependence in the laboratory (Yanagita, 1978, Lanier et al, 2010, epidemiological and postmarketing surveillance of tramadol reports low abuse and diversion since its introduction in the United States in 1994 (Cicero et al, 1999, 2005, Woody et al, 2003Inciardi et al, 2006). Modest opioid agonist activity in an oral product is desirable for opioid withdrawal treatment.…”
Section: Introductionsupporting
confidence: 71%
“…• Tramadol has good efficacy [5,6,13] in detoxification and relapse prevention in patients with moderate level of opioid dependence as compared to buprenorphine [15].…”
Section: Summary /Discussionmentioning
confidence: 99%
“…The O-demethylated metabolite, (+)-O-demethyltramadol (known as M1), has greater affinity for the mu-opioid receptor than the parent compound and is responsible for tramadol's mu-opioid activity, and is primarily due to its binding to the micro receptor [1]. Despite this micro receptor activity, tramadol appears to have low abuse potential and was approved as an unscheduled analgesic in the USA in 1994 based largely on epidemiologic experience, and a number of animal and human [2][3][4] studies suggested, it had low abuse potential. The pharmacologic profile of tramadol makes it a candidate for opiate withdrawal treatment; Whereas Buprenorphine has high abuse potential.…”
Section: Introductionmentioning
confidence: 99%
“…Важные данные, подтверждающие такую возможность, получены в недавнем исследовании не-мецких ученых [57], в котором участвовали 9 пациентов с опиоидной зависимостью, принимавших трамадол в дозе 200 или 800 мг/сут. В ходе двойного слепого РКИ они полу-чали плацебо, налоксон (антагонист опиодиов) или гидро-морфон.…”
Section: « д е с я т ь ш а г о в » : а л г о р и т м д л и т е л ь н unclassified